Penilaian Risiko Operasional Pada Pembuatan Perahu Fiberglass Di Galangan Kapal Cv Era Fiberboat Menggunakan Metode Matrik Risiko Dan Fmea - Cesar Ivan Nugraha; Minto Basuki (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The purpose of this study is to analyze the safety operational process in fiberglass shipbuilding, identify the types of risk causes that hinder the construction of fiberglass boats and propose recommended actions needed to overcome the risks in CV ERA FIBERBOAT by using theoretical research methods. Identification of risks in the process of building new ships, namely employees, materials, work equipment, payment of construction costs, working drawings have revisions. Determining the risk rating of the new ship building process: very high; inappropriate equipment, height; late payment / paying, medium; working drawings have revisions, low; materials arrive late, very low; employees procrastinate. Mitigating risks in the process of building new ships: employees delay work with mitigation, namely the director of the company provides the opportunity for employees to rest so that employees do not get sick, materials arriving late are mitigated by means of shipyard companies providing an easy-to-find address point so that the sender of materials does not having difficulty finding the address of the shipyard, working drawings have revisions that can be mitigated by means the company must always make an existence to the customer in every work process so that there is no miscommunication